Quantifying the cost and benefits of ending hunger and undernutrition: Examining the differences among alternative approaches - Fan, Shenggen; Headey, Derek D.; Laborde Debucquet, David; Mason-D'Croz, Daniel; Rue, Christopher; Sulser, Timothy B.; Wiebe, Keith D. (International Food Policy Research Institute, 2018)
This brief examines estimates produced by several recent model simulations and frameworks that focus on the cost of ending hunger as well as progress toward other development goals—estimates that range from US$7 billion to US$265 billion per year. The differences among these estimates are largely attributable to the different targeted objectives and policy questions of each modeling exercise, different investment strategies considered, and varying assumptions about the role of different sectors in reducing hunger.